Diagnostic and Complication Rate of Image-guided Lung Biopsies in Raigmore Hospital, Inverness: A Retrospective Re-audit - Khadka, S (Nepalese Journal of Radiology, 2012)
Background: Suspected lung malignancies that are deemed inaccessible by bronchoscopic biopsy undergo image-guided biopsies to obtain samples for histological study. A previous audit performed in 2008 assessed the diagnostic and complication rate of computed tomography (CT)-guided lung biopsies. This retrospective re-audit aimed to reassess the lung biopsies done in 2010. Standards: British thoracic society guidelines for Radiologically guided lung biopsy. Materials and Method: All patients who underwent image-guided lung biopsies at Raigmore Hospital, Inverness, in 2010 were included in the study. The imaging was either CT or ultrasound (US) and either fine-needle aspirate or core-biopsy samples were collected. Information on diagnostic rate, complications such as pneumothorax and haemoptysis, age, sex, size and depth of lesion were collected. Results: 108 biopsies were obtained by image guided lung biopsies from 101 patients during 2010. 80 lesions were malignant, 19 were benign and 2 undiagnostic. 7 biopsies had to be repeated. Diagnostic accuracy was 91.7% (99 biopsies). 21 patients (19.4%) had pneumothorax. 19 suffered from small pneumothorax while 2 (1.9%) required chest drain. 7 patients (6.5%) developed minor haemoptysis. Only 3 out of 108 biopsies were done under US scan. Conclusion: The diagnostic and pneumothorax rates are well within British thoracic society guidelines, whilst the minor haemoptysis rate is slightly higher. Further large-scale studies are indicated to assess the possible role of ultrasound as a potential imaging method for pleural based lung biopsies. DOI: http://dx.doi.org/10.3126/njr.v1i1.6315 Nepalese Journal of Radiology Vol.1(1): 1-7